1982
DOI: 10.1007/bf00589094
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate transport in brush border membrane vesicles isolated from renal cortex of young growing and adult rats

Abstract: Recent clearance studies have demonstrated that the maximal tubular reabsorption of inorganic phosphate (Pi) per ml of glomerular filtrate (max. TRPi/ml GF) of the whole kidney is markedly lower in adult than in young growing rats fed either normal (0.8 g %) or low (0.2 g %) phosphorus diet. In addition, in adult rats clearance studies indicate that enhancement of max. TRPi/ml GF is observed 21 days but not 8 days after starting the low (0.2%) phosphorus diet. In the present work we have studied in the same ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…We also show that Npt2 -/-mice fail to exhibit an increase in BBM Na + /Pi cotransport in response to Pi deprivation, thereby documenting the crucial role of Npt2 in the renal adaptive response to low Pi intake. Previous studies have provided evidence for higher Na + /Pi cotransport activity in BBMs from younger animals when compared with older animals, consistent with the notion that the requirement for Pi is increased during growth (30,31,38). Although it was suggested that the higher transport activity observed in weanling rats, relative to 3-month-old rats, is mediated by a Na + /Pi cotransporter that is distinct from, but related to, Npt2 (30), this growth-related Na + /Pi cotransporter has not yet been identified at the molecular level.…”
supporting
confidence: 73%
“…We also show that Npt2 -/-mice fail to exhibit an increase in BBM Na + /Pi cotransport in response to Pi deprivation, thereby documenting the crucial role of Npt2 in the renal adaptive response to low Pi intake. Previous studies have provided evidence for higher Na + /Pi cotransport activity in BBMs from younger animals when compared with older animals, consistent with the notion that the requirement for Pi is increased during growth (30,31,38). Although it was suggested that the higher transport activity observed in weanling rats, relative to 3-month-old rats, is mediated by a Na + /Pi cotransporter that is distinct from, but related to, Npt2 (30), this growth-related Na + /Pi cotransporter has not yet been identified at the molecular level.…”
supporting
confidence: 73%
“…The limited capacity of senescent animals to adapt to a hypophosphatemic environment (Caverzasio et al, 1982a;Kiebzak and Sacktor, 1986) was retained by the cultured renal cells in the present study. We showed that renal cells respond to a 24-hour phosphate deprivation by increasing phosphate uptake by 46% and 24% of their corresponding controls in young and adult cell preparations, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…The Pi uptake by preparations of BBM vesicles shows that the PCT PiR is regulated by the Pi content of the diet during the 3rd postnatal wk, as it is in older growing rats and adult rats (7,(27)(28)(29)(30). The initial rate of intravesicular accumulation was higher in LPD than in NPD rats and lower in HPD rats.…”
Section: Animalsmentioning
confidence: 89%
“…This might be compared to the hypercalciuria observed in the Pi depletion of premature infants fed human milk (26). The greater sensitivity of young growing rats to an LPD compared to adult animals (6,7,27) may be attributed to the fact that, for a given Pi deprivation, Pi depletion is much greater in these young growing animals. Lastly, the slight hypomagnesemia of LPD rats, without the increase in the FE of this ion that normally occurs in Pi depletion, suggests that these rats were also suffering from magnesium depletion.…”
Section: Animalsmentioning
confidence: 99%